2016
DOI: 10.2320/matertrans.m2016188
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Behavior of Pure Cu and Cu-Ni-Si Alloy Evaluated by Micro-Tensile Testing

Abstract: Micro-tensile tests of pure copper and a precipitation strengthening-type Cu alloy, Cu-Ni-Si alloy, were performed using micro-sized tensile specimens with 10 × 10 µm 2 in cross-section and 40 µm in length and a micro-gripper, which were fabricated by a focused ion beam system. The obtained experimental results were compared with the results of Cu-Ni-Si alloy bulk sample. The micro-tensile tests of both pure Cu and Cu-Ni-Si alloy showed the typical serrations caused by moving of dislocations and a decrease of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
1
7
1
Order By: Relevance
“…In SIM images of all of the deformed micropillars, thin, curvy and numerous slip lines with some small protrusion were observed. This tendency was also observed in pure Cu specimen which grains were constrained by grain boundaries [15].…”
Section: Mechanical Behavior By Microcompression Testsupporting
confidence: 61%
See 4 more Smart Citations
“…In SIM images of all of the deformed micropillars, thin, curvy and numerous slip lines with some small protrusion were observed. This tendency was also observed in pure Cu specimen which grains were constrained by grain boundaries [15].…”
Section: Mechanical Behavior By Microcompression Testsupporting
confidence: 61%
“…In the microtensile study [15], typical serrations during the plastic deformation were observed in the S E -S E curve. However, in the compression test, serrations were not observed and the curve is similar to the results obtained with a bulk specimen.…”
Section: Mechanical Behavior By Microcompression Testmentioning
confidence: 93%
See 3 more Smart Citations